2017
DOI: 10.1177/2325967117700589
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Lateral Center-Edge Angle and 3-Dimensional Acetabular Coverage

Abstract: Background:The lateral center-edge angle (LCEA) is an important measurement in understanding acetabular morphology and has had multiple interpretations. Misunderstanding of the LCEA and its relationship with acetabular 3-dimensional (3D) morphology may result in misdiagnosis and poor outcomes.Purpose:To determine the discrepancy between bone-edge and sourcil-edge LCEA measurements on anteroposterior (AP) radiographs and to determine the 3D anatomic location of the sourcil-edge and bone-edge LCEA measurements.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 19 publications
3
40
0
Order By: Relevance
“…However, previous studies have reported that the inclination of the pelvis in the sagittal plane (pelvic sagittal inclination [PSI]) changes with patient posture and is altered after hip surgery. Understanding how PSI changes in several postures is important as it affects the measurements of femoral head coverage 1‐4 as well as the functional location of the acetabular cup in the setting of total hip arthroplasty (THA) 5,6 . As abnormal changes in PSI lead to progression of hip osteoarthritis and dislocation of the hip, 7,8 many studies have quantified PSI in different postures, with some of these including a large clinical cohort, 8,9 and a postoperative period of more than 10 years 10 …”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have reported that the inclination of the pelvis in the sagittal plane (pelvic sagittal inclination [PSI]) changes with patient posture and is altered after hip surgery. Understanding how PSI changes in several postures is important as it affects the measurements of femoral head coverage 1‐4 as well as the functional location of the acetabular cup in the setting of total hip arthroplasty (THA) 5,6 . As abnormal changes in PSI lead to progression of hip osteoarthritis and dislocation of the hip, 7,8 many studies have quantified PSI in different postures, with some of these including a large clinical cohort, 8,9 and a postoperative period of more than 10 years 10 …”
Section: Introductionmentioning
confidence: 99%
“…56,60 It is important to distinguish precisely between W-CEA and L-CEA. 17,59,61,62 The W-CEA represents the weightbearing supero/lateral coverage and the L-CEA expresses the bony acetabular extension laterally.…”
Section: Acetabular Assessmentsmentioning
confidence: 99%
“…10c). The location of point E on the lateral margin of the weightbearing zone may be difficult to determine; by CT, it is located where the concave acetabular roof ends laterally 56,61 or at the lateral margin of the dense subchondral bone. 56 On MRI, the point of the transition between the acetabular cartilage and the labrum was suggested.…”
Section: Acetabular Assessmentsmentioning
confidence: 99%
“…Using this coordinate system, the nodes of the femoral head were sorted into quadrants about the transverse axis ( Fig. 2C) (Harris et al, 2014;Wylie et al, 2017).…”
Section: Analysis Of Total and Regional Femoral Head Coveragementioning
confidence: 99%
“…A major limitation of these prior studies is that 3-D coverage was based on reconstructions of volumetric images acquired in the supine position. Previous 2-D radiographic studies found a difference in coverage among supine and standing positions (Henebry and Gaskill, 2013;Pullen et al, 2014;Wylie et al, 2017). Thus, it follows that femoral head coverage could change during gait, but these measurements are not available.…”
Section: Introductionmentioning
confidence: 96%